2002
DOI: 10.1046/j.1528-1157.2002.26001.x
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Anterior Thalamus Stimulation for Intractable Epilepsy

Abstract: Summary:Purpose: A significant number of patients with epilepsy remain poorly controlled despite antiepileptic medication (AED) treatment and are not eligible for resective surgery. Novel therapeutic methods are required to decrease seizure burden in this population. Several observations have indicated that the anterior thalamic region plays an important role in the maintenance and propagation of seizures. We investigated neuromodulation of the anterior thalamus by using deep-brain stimulation (DBS) in patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
377
2
5

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 537 publications
(405 citation statements)
references
References 19 publications
12
377
2
5
Order By: Relevance
“…The treatment group of the 110 patients in the SANTE trial showed a median seizure frequency reduction of 29% at 3 months, 41% at 1 year, 56% at 2 years, and 68% by the end of 3 years as compared with baseline. Other, smaller, nonrandomized trials of ANT stimulation also have been performed with 4–6 patients per trial, with seizure frequency reduction of 14–75% 9, 11, 16, 17, 18, 19…”
Section: Discussionmentioning
confidence: 99%
“…The treatment group of the 110 patients in the SANTE trial showed a median seizure frequency reduction of 29% at 3 months, 41% at 1 year, 56% at 2 years, and 68% by the end of 3 years as compared with baseline. Other, smaller, nonrandomized trials of ANT stimulation also have been performed with 4–6 patients per trial, with seizure frequency reduction of 14–75% 9, 11, 16, 17, 18, 19…”
Section: Discussionmentioning
confidence: 99%
“…It has also been used to treat various other neurological conditions including depression (Mayberg et al, 2005), obsessive-compulsive disorder (Gabriels et al, 2003) and epilepsy (Hodaie et al, 2002). Despite the general effectiveness of DBS, its clinical applications have preceded scientific understanding of its mechanism(s) of action (McIntyre et al, 2004a).…”
Section: Deep Brain Stimulation (Dbs) Is An Established Therapy For Tmentioning
confidence: 99%
“…In addition, DBS shows promise in the treatment of epilepsy (Hodaie et al, 2002), obsessive-compulsive disorder (Gabriels et al, 2003), and depression (Mayberg et al, 2005). However, the clinical successes of DBS are tempered by our limited understanding of the effects of DBS on the nervous system.…”
Section: Introductionmentioning
confidence: 99%